Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.3390/mi11121073
|View full text |Cite
|
Sign up to set email alerts
|

Electro-Optical Properties of Sputtered Calcium Lead Titanate Thin Films for Pyroelectric Detection

Abstract: We report the deposition and characterization of calcium lead titanate (PCT) thin films for pyroelectric detectors. PCT films of thicknesses ranging from ~250 to 400 nm were deposited on both silicon and Si/SiN/Ti/Au substrates at 13 mTorr pressure by 200W radio frequency sputtering in an Ar + O2 environment. Substrates were kept at variable temperatures during the deposition. The PCT films were annealed at various temperatures in an O2 environment for 15 min. X-ray diffraction results confirm the polycrystall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Modified PT materials have shown interesting piezoelectric [ 15 ] and pyro-electric properties. Preparation and characterization of many modified versions of PT films including Calcium (Ca) or Calcium Lead Titanate (PCT) [ 16 ], Lanthanum (La)-modified PT (PLT) [ 17 ], and La modified Lead Zirconate Titanate (PLZT) [ 18 ] has been reported. Magnetron sputter deposition has also been used to synthesize layered perovskite films.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Modified PT materials have shown interesting piezoelectric [ 15 ] and pyro-electric properties. Preparation and characterization of many modified versions of PT films including Calcium (Ca) or Calcium Lead Titanate (PCT) [ 16 ], Lanthanum (La)-modified PT (PLT) [ 17 ], and La modified Lead Zirconate Titanate (PLZT) [ 18 ] has been reported. Magnetron sputter deposition has also been used to synthesize layered perovskite films.…”
Section: Methodsmentioning
confidence: 99%
“…Any increase in the oxidation rate of the Pb adatoms during film growth reduces the re-evaporation rate of the Pb adatoms. According to Schlom et al [67] the amount of the Pb re-evaporation diminishes when the gas mixture includes highly oxidizing gas(es) such as ozone and/or N 2 O. E. Mafi et al [16] reported on the preparation and characterization of crack-free PCT thin films with smooth surfaces for use in pyroelectric detectors. PCT films were deposited on both silicon and Si/SiN/Ti/Au substrates at 13 mTorr pressure of a gascontaining mixture of Ar 2 and O 2 using a 200 W-RF sputtering source for four hours at 550 • C < Ts < 800 • C. The PCT films were then annealed at Tpan = 550, 600, 650 and 700 • C in O 2 environment for small time intervals of 15 min.…”
Section: Growth Dimension Depletive Nucleation Constant Nucleationmentioning
confidence: 99%
See 3 more Smart Citations